Combined oral contraceptive use is associated with both improvement and worsening of mood in the different phases of the treatment cycle—A double-blind, placebo-controlled randomized trial. (February 2017) - Lundin, Cecilia; Danielsson, Kristina Gemzell; Bixo, Marie; Moby, Lena; Bengtsdotter, Hanna; Jawad, Izabella; Marions, Lena; Brynhildsen, Jan; Malmborg, Agota; Lindh, Ingela; Sundström Poromaa, Inger
Highlights: Combined oral contraceptive is associated with small increases in anxiety, irritability, and mood swings during the intermenstrual phase. The adverse mood symptoms were most pronounced in the subgroup of women who reported previous side effects. A significant premenstrual improvement in depression was noted. The proportion of women who reported significant deterioration did not differ between treatments. Abstract: Objective: Ever since the introduction of combined oral contraception (COC), one of the major reasons for discontinuing the pill use has been mood-related side effects. Moreover, women who discontinue the pill turn to less effective methods whereby the probability of an unintended conception increases. Approximately 4–10% of COC users complain of depressed mood, irritability or increased anxiety, but drug-related causality has been difficult to prove. Given the lack of randomized controlled trials in this area, we aimed to prospectively estimate the severity of adverse mood in COC users that would be as representative of general users as possible. Methods: This investigator-initiated, multi-center, randomized, double-blinded, placebo-controlled study included 202 healthy women. Women were randomized to a COC (1.5 mg estradiol and 2.5 mg nomegestrolacetate) or placebo for three treatment cycles. Main outcome measure was the Daily Record of Severity of Problems (DRSP), which was filled out daily during one baseline cycle and the final treatment cycle. Results: Results from 84 women in the COC group and 94 women in the placebo group were analysed. COC use was associated with small, but statistically significant, increases in mean anxiety (0.22; 95% CI: 0.07–0.37, p = 0.003), irritability (0.23; 95% CI: 0.07–0.38, p = 0.012), and mood swings scores (0.15; 95% CI: 0.00–0.31, p = 0.047) during the intermenstrual phase, but a significant premenstrual improvement in depression (−0.33; 95% CI: −0.62 to −0.05, p = 0.049). Secondary analyses showed that women with previous adverse hormonal contraceptive experience reported significantly greater mood worsening in the intermenstrual phase in comparison with healthy women, p < 0.05. The proportion of women who reported a clinically relevant mood deterioration did not differ between those allocated to COC (24.1%) or placebo (17.0%), p = 0.262. Conclusion: COC use is associated with small but statistically significant mood side effects in the intermenstrual phase. These findings are driven by a subgroup of women who clearly suffer from COC-related side effects. However, positive mood effects are noted in the premenstrual phase and the proportion of women with clinically relevant mood worsening did not differ between treatment groups.